Impact of Innovativeness and Total Quality Management (TQM) on Operational Performance Trough Competitions in XXX Company - Wijaya, Rudi; Lukman, Syukri; Amali Rivai, Harif (DINASTI RESEARCH, 2024)
This research aims to determine the influence of innovativeness and total quality management (TQM) on operational performance through competitive advantage at company XXX. This type of research is quantitative. The sampling method used in this research is probability sampling so the total sample in this research is 164 respondents. The data analysis technique in this research uses descriptive statistical analysis and structural equation modeling (SEM). The results of Innovativeness (X1) have no effect on Competitive Advantage (Z), Innovativeness (X1) has a positive and significant effect on Operational Performance (Y), Total Quality Management (X2) has no effect on Competitive Advantage (Z), Total Quality Management (X2 ) has a positive and significant effect on Operational Performance (Y), Competitive Advantage (Z) has a positive and significant effect on Operational Performance (Y), Innovativeness (X1) has a positive and significant effect on Operational Performance (Y) through Competitive Advantage (Z) and Total Quality Management (X2) has no effect on Operational Performance (Y) through Competitive Advantage (Z) at Company XXX.